PENGARUH GAJI, TUNJANGAN DAN PELATIHAN KERJA TERHADAP KINERJA KARYAWAN DI PT. ANGGRAENI PERDANA CILACAP - Werdiasih, Rustina Dewi; Eri Aqmarina (JURNAL EKONOMI, 2019)
The success of a company is strongly influenced by the performance of employees, each company will definitely try to improve employee performance in order to achieve the company's goals to the fullest. Maharjan (2012) states that performance is a result achieved because it is motivated by work and satisfied with the work they do. Efforts to improve employee performance include increasing salaries, benefits and job training for employees. This study aims to determine the effect of salary (X1), allowance (X2) and job training (X3) to Employee Performance (Y) at PT. Anggraeni Perdana Cilacap. In this study using a sample of 52 employee respondents who were in PT. Anggraeni Perdana Cilacap. For sampling in this study using the total sampling method. To find out the magnitude of the effect of salary, benefits and job training on employee performance, multiple linear regression analysis is used. To test the effect as a whole, F test is used with degrees of freedom (df) = k and (n-k-2) with a level of confidence (Î± = 0.05). To determine the effect partially used T test with degrees of freedom (df) = k and (n-k-2) with a level of confidence (Î± = 0.05). Based on the results of the T test obtained t count variable salary variable t count of 1.840> 1.67655 hypothesis accepted. Allowance variable of tcount value of 0.540 1,67655 hypothesis is accepted. The results of the analysis were obtained by calculating the F value greater than F table, namely Fcount 8.923> 2.79. The conclusion of this study, based on the results of the study the most dominant variable affects employee performance, namely job training with a Î² coefficient of 0.389. The determination coefficient value of Adjusted R Square is 0.318. This means that 31.8% of employee performance variables can be explained by salary variables (X1), allowances (X2) and job training (X3) while 68.2% is influenced by other factors outside the research model. Keywords: Salary, Allowances, Job Training, Employee Performance